2019
DOI: 10.1002/hpm.2789
|View full text |Cite
|
Sign up to set email alerts
|

Performance of care for end‐of‐life cancer patients in Tuscany: The interplay between place of care, aggressive treatments, opioids, and place of death. A retrospective cohort study

Abstract: Summary Supportive and palliative care at the end of life (EOL) is a core component of health systems. Providing care at the EOL may require the interaction of several care providers working in different settings including nursing homes, home care, hospices, and hospitals. This work aims to (a) provide evidence on the performance of EOL care for cancer patients across healthcare organizations, with a focus on the place of care, aggressive treatments, opioids, and the place of death and (b) analyze factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
2
2
1
Order By: Relevance
“…Our study supports the evidence from previous investigations that PC admission has a relevant role in reducing various indicators of EOL aggressive care 5–14. In particular, we found that PC reduced hospitalisations by over 70%, long hospital stay by 75%, ED visit by 65%, and use of chemotherapy by 35% during the last month.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study supports the evidence from previous investigations that PC admission has a relevant role in reducing various indicators of EOL aggressive care 5–14. In particular, we found that PC reduced hospitalisations by over 70%, long hospital stay by 75%, ED visit by 65%, and use of chemotherapy by 35% during the last month.…”
Section: Discussionsupporting
confidence: 91%
“…With reference to the indicators of aggressive EOL care analysed in our study, we found that about 45% of patients were hospitalised during the last 30 days of life, a value that is within the range between 40% and 65% reported in previous investigations 10–14 28. About 30% of patients with cancer in Lombardy died in hospital, a value among the lowest reported in other studies (between 30% and 70%) 4 10 11 13–15 17 28.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations